The Enormous Power of Protervity and Social Corruption, a Possible Remission - Leandro Meléndez Lugo (Research Developments in Arts and Social Studies Vol. 1, 2022)
The main objective of this work, has been to highlight the main cause why individuals, on a world scale, have entered into a swampy terrain, figuratively speaking, which seems to have no end. It is proposed to elucidate and reduce the main cause for this contradiction, since modern civilisation should have a better social integration. After an insightful analysis, a heartless power, which in many cases is acquired through large amounts of money, very often determines not only the world’s agenda, but also much of the lives of millions of people, is here identified and characterised. In this power, which is sometimes unseen, and mainly held unlawfully by some business owners and partnerships, within which in many ways all of us participate, by putting money in first place over anything else and making it an end in itself. The most effective weapon that uses this power for its own purposes is social corruption. I show here in some way how society, influenced by this power, ignores the individual and how the individual becomes an enemy of his own organisation, which is the society. It is explained how society as we know it is in danger of extinction and how we could remedy this knotted tribulation, that the evil power itself is not interested in repressing. When the social arrangement is broken by either party, i.e. the citizen or the society disrupts this social pact, an act of corruption has been committed. Corruption is a wicked behaviour and can be known as “the act of spoiling”. I also present here a recipe that is aimed at reducing social corruption to a tolerable level.